Faktor Faktor yang Berhubungan dengan Perilaku Kesulitan Makan Anak Prasekolah di Kota Ambon - Lameky, Vernando Yanry; Wakanno, Grace Jeny (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
Eating difficulties in preschool children are a problem that can affect their growth and development. This study analyzes factors related to eating difficulties in preschool children in Ambon City. This study used a descriptive design with a quantitative approach. The study sample sample was 40 preschool children selected using a purposive sampling technique. Data were collected through questionnaires filled out by parents and analyzed using the chi-square test. The results showed that child involvement, parental eating behavior, food provision, and food control were significantly related to eating difficulties in preschool children (p-value <0.05). Parental eating behavior strongly influences children's eating patterns, followed by poor food provision. Children who were not involved in choosing food, as well as those whose parents had unhealthy eating patterns, were at higher risk of experiencing eating difficulties. These results indicate the importance of educating parents about healthy eating patterns and more flexible feeding strategies to prevent eating difficulties in children.